«Ten Questions a Hundred Famous Russian People» as Format Student Television Broadcasting - M. N. Kim (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to the problems of designing television broadcasting for students NWIM RANEPA by example implementation of the television project «Ten questions a hundred famous Russian people». This media product has its own unique. It is created from beginning to the end by the students themselves, studying in the field of training “Journalism” NWIM RANEPA. The authors of the article comprehensively analyzed all technological and creative aspects of this project. In their opinion, the project «Ten questions a hundred famous Russian people» became an experimental platform where the most brave decisions and approaches in studying autobiographies of famous people were tested, where students can engage in self-directed practice activities and mastering of various television specialties: cameraman, producer, TV presenter, editor, sound engineer, screenwriter, correspondent, editor. Therefore the project harmonically joined in the educational process to carry out educational and enlightening functions.